Gandhi CEO - "Axelrod, Alan" (New Delhi, 2010)
Fourteen lessons to instruct, inspire, and encourage$1! = (BHistory$1 (Bs great leaders have much to teach us, and no one outshines Alan Axelrod in extracting those lessons and applying them to today$1 (Bs business world. His Elizabeth I, CEO and Patton on Leadership both became BusinessWeek bestsellers$1 (Band now, to follow his recent Winston Churchill, CEO, Axelrod has found a new and perhaps surprising subject for his popular format: Gandhi. Gandhi, a CEO? Absolutely$1 (Band an incomparable example for our uncertain times, when we need leaders we can trust and admire. Not only was he a moral and intensely spiritual man, but also a supremely practical manager and a powerful agent for change, able to nurture the rebirth of an entire nation. To achieve this goal, he mastered the elements of personal leadership and institutional management. Axelrod looks at this much-studied figure in a way nobody has before, employing his fluid, engaging, and conversational style to bring each lesson to life through quotes and vivid examples from Gandhi$1 (Bs life.s
Keywords: Gandhism